A new approach for generating efficient solutions within the goal programming model - Larbani, Moussa; Aouni, Belaid (Palgrave Macmillan Ltd., 2011)
This paper deals with the issue of efficiency in the Goal Programming (GP) model. A general approach for the determination of an efficient solution of GP is presented. An efficiency test for the GP solution is developed; moreover, when this solution is not efficient, an efficient solution that dominates it is determined